Strategi Pola Asuh Orang Tua dalam Pembentukan Generasi Anak-Anak Kristen - Peramita, Nia (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to reveal parenting strategies in shaping the character of Christian children's faith amidst the challenges of the modern era. Using a descriptive qualitative approach and data collection techniques through observation, interviews, and documentation, this study was conducted in a local church environment. The findings show that Christian parents implement three main strategies, namely: exemplary living based on the teachings of Christ, spiritual discipline through family worship activities, and creating quality time with children. Despite facing challenges such as busy work, the influence of digital media, and inconsistent behavior, most parents still try to evaluate themselves and maintain the values ​​of faith in the household. Effective parenting is not only instructional, but also relational and spiritual, emphasizing the importance of the role of parents as real life role models. The results of this study are expected to be a reference for churches, Christian schools, and parent communities in developing strategies for fostering children's faith in a sustainable manner amidst the dynamic development of the era.